Talpa europaea_C2_1000% - Lauridsen, Henrik; Hansen, Kasper; Nørgård, Mathias Ø.; Wang, Tobias; Pedersen, Michael (Dryad Digital Repository, 2016)
Ready to 3D print STL file of Talpa europaea C2 (axis).